L’Appel du vide : l’espace vide de Peter Brook et l’épuisement beckettien - Sophie MARUÉJOULS-KOCH (E-REA)
An interval of about twenty years separates Peter Brook’s The Empty Space from Gilles Deleuze’s “The Exhausted.” The first is a book about theatre practice and the need for new forms, the second is a theoretical examination of four of Samuel Beckett’s television plays. Their comparison provides a starting point for this study, first because Brook’s and Deleuze’s conceptions of the notion of emptiness as a potential for creation converge in many respects and second because both texts echo each other in a way that allows for a deeper analysis of the image as a concept Deleuze considered to be the aim of art. Brook and Beckett are minimalist artists who remove, reduce and subtract to create an image stripped down to the bone, the form of something essential, the thing that remains after everything else has disappeared. The aim is to follow that trace through Brook’s and Beckett’s work in order to draw its contours and to see in what way exactly the work of the two Post-War artists meet, how emptiness and exhaustion allow them to create a form beyond language that reaches the spectator, placing her face to face with the mystery of life, with something beyond that is all contained within the image of the face.